The use of wildlife by sambaquianos in prehistoric Babitonga Bay, North Coast Of Santa Catarina, Brazil - Rocha Bandeira, Dione da (Revista Chilena de Antropología, 2016)
The study of faunal remains from archaeological sites is based on qualitative and quantitative data that contribute to our understanding of the consumption of animal protein, environment, and lifestyle often goes beyond understanding daily activities. Indeed, faunal remains in archaeological sites vary among societies, as choices are both availability and culturally defined. Here I discuss available faunal data from shell mounds in the Babitonga Bay, in conjunction with the presence of pottery in some of their archaeological layers. Forte Marechal Luz, Enseada I, Bupeva II and Itacoara sites have pottery and two different stratigraphic horizons. The results show some interesting differences in taxa and quantity of the animal remains, when the different layers of the same site and between sites are compared. I discuss cultural identity and diversity of the prehistoric dwellers living in the Babitonga Bay, in the light of a relatively late introduction of ceramics that affected less than 10% of the shell mounds in the area.